Next-generation catalysts for sustainable biodiesel production: a comprehensive review - Olusola David Ogundele (Romanian Journal of Ecology & Environmental Chemistry)
Biodiesel, derived from renewable biomass, has emerged as a promising solution, particularly microalgae-based biodiesel, which offers high lipid productivity, CO2 sequestration, and the ability to grow in non-arable land and wastewater. However, the commercialization of biodiesel faces challenges, including high production costs, energy-intensive processes, and scalability issues. This review explores the role of catalysts in biodiesel production, focusing on conventional homogeneous and heterogeneous catalysts, as well as next-generation catalysts such as nanocatalysts, enzymatic catalysts, and bifunctional catalysts. These advanced catalysts offer higher efficiency, reusability, and reduced environmental impact, aligning with Sustainable Development Goals (SDGs) 7 (Affordable and Clean Energy), SDG 13 (Climate Action), and SDG 12 (Responsible Consumption and Production). The integration of microalgae cultivation with biorefineries and waste streams, such as wastewater and flue gas, enhances sustainability by reducing costs and minimizing environmental impact. By addressing technical, economic, and environmental barriers, microalgae-based biodiesel can play a significant role in the global transition to a sustainable and low-carbon energy future, contributing to the achievement of multiple SDGs. This review highlights the potential of next-generation catalysts to revolutionize biodiesel production and underscores the importance of interdisciplinary research and policy frameworks in realizing this potential.